2016
DOI: 10.1016/j.neuroimage.2015.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of effective connectivity during memory encoding and retrieval differ between patients with mild cognitive impairment and healthy older adults

Abstract: Previous research has shown that there is considerable overlap in the neural networks mediating successful memory encoding and retrieval. However, little is known about how the relevant human brain regions interact during these distinct phases of memory or how such interactions are affected by memory deficits that characterize mild cognitive impairment (MCI), a condition that often precedes dementia due to Alzheimer’s disease. Here we employed multivariate Granger causality analysis using autoregressive modeli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 102 publications
4
24
0
Order By: Relevance
“…Thus, effective connectivity methodology can be used to estimate the direction and magnitude of influence between brain regions (Friston, ), such as between the HC and other DMN nodes. Examining the link between CRF and hippocampal effective connectivity is of importance, given that previous studies employing effective connectivity techniques have demonstrated that activation of the HC influences the activation of other brain regions, specifically during tasks involving episodic (Hampstead, Khoshnoodi, Yan, Deshpande, & Sathian, ) and autobiographical memory (McCormick, St‐Laurent, Ty, Valiante, & McAndrews, ; St. Jacques, Rubin, & Cabeza, ). Investigating how CRF interacts with effective connectivity between the nodes of the DMN, including the HC, provides a unique opportunity to examine this question.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, effective connectivity methodology can be used to estimate the direction and magnitude of influence between brain regions (Friston, ), such as between the HC and other DMN nodes. Examining the link between CRF and hippocampal effective connectivity is of importance, given that previous studies employing effective connectivity techniques have demonstrated that activation of the HC influences the activation of other brain regions, specifically during tasks involving episodic (Hampstead, Khoshnoodi, Yan, Deshpande, & Sathian, ) and autobiographical memory (McCormick, St‐Laurent, Ty, Valiante, & McAndrews, ; St. Jacques, Rubin, & Cabeza, ). Investigating how CRF interacts with effective connectivity between the nodes of the DMN, including the HC, provides a unique opportunity to examine this question.…”
Section: Introductionmentioning
confidence: 99%
“…Both studies were illustrated with application to task-based fMRI. Other studies have applied dynamic EC to task-based fMRI as well [Feng et al, 2015;Grant et al, 2014Grant et al, , 2015Hampstead et al, 2016;Hutcheson et al, 2015;Libero et al, 2015;Wheelock et al, 2014].…”
Section: Introductionmentioning
confidence: 99%
“…This raises the possibility that dynamic alterations in resting state EC cannot be ignored and needs to be investigated. However, to the best of our knowledge, there has been scant literature on dynamic EC of resting state fMRI (but see Jin et al, 2017;Zhao et al, 2017;Rangaprakash et al, 2018), and most investigations of dynamic EC have focused on taskbased fMRI (Sato et al, 2006;Havlicek et al, 2010;Grant et al, 2014Grant et al, , 2015Lacey et al, 2014;Wheelock et al, 2014;Hutcheson et al, 2015;Feng et al, 2016Feng et al, , 2018Hampstead et al, 2016;Wang et al, 2017;Ramaihgari et al, 2018;Rao et al, 2018).…”
Section: Introductionmentioning
confidence: 99%